Effect of Phytate Phosphorus on the Utilisation of Rice Bran in Broiler Chickens) - Ukil, Md. Asaduzzaman (1999)
Rice bran (RB) is a by-product of rice milling industry and is produced in many parts of the world including Malaysia. It is a high energy source for both ruminant and nonruminant animals with a crude protein content of 12-13%. Its fibre content is about 7-16%. Rice bran is also rich in phytate phosphorus (pP) which is not easily available to poultry. This study examines the utilisation of pP by broiler chickens fed RB based diets at the finishing stage. The role of phytase enzyme and vitamin D3 in improving the utilisation of pP was also examined. Two growth trials were carried out with 21 day-old broiler chickens to determine the effects of replacing com with RB on their performance. It was found that the performance of birds were adversely affected when RB was included at 45% level. The results obtained from these two studies suggest that RB can be included up to 35% in the diet of broiler chicken without any adverse effects on their performance.